2008
DOI: 10.1111/j.1600-0722.2008.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osterix in mechanical stress‐induced osteogenic differentiation of periodontal ligament cells in vitro

Abstract: Osterix (Osx) is an osteoblast-specific transcription factor required for the differentiation of pre-osteoblasts into functional osteoblasts. This study sought to examine the changes of Osx expression in periodontal ligament cells (PDLC) subjected to mechanical force, and to investigate whether Osx is involved in the mechanical stress-induced differentiation of PDLC. Human PDLC were exposed to centrifugal force for 1-12 h. Real-time polymerase chain reaction (PCR), western blot, and immunofluorescence assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Many pivotal genes in mineralization of the bone matrix such as collagen 1 (a1), bone sialoprotein, osteopontin, and osteocalcin were regulated by Sp7. (26,27) Furthermore, Baek and colleagues (28) have concluded that Sp7 continues to be required for bone formation in growing and adult bones. Due to this critical regulation of the osteoblast phenotype by Sp7, identifying upstream regulators of this gene is the key to our understanding of osteoblast mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Many pivotal genes in mineralization of the bone matrix such as collagen 1 (a1), bone sialoprotein, osteopontin, and osteocalcin were regulated by Sp7. (26,27) Furthermore, Baek and colleagues (28) have concluded that Sp7 continues to be required for bone formation in growing and adult bones. Due to this critical regulation of the osteoblast phenotype by Sp7, identifying upstream regulators of this gene is the key to our understanding of osteoblast mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences also indicate that p38 activity modulates Osx expression induced by BMP in calvarial as well as bone marrow-derived mesenchymal stem cells (17,20,24,27). Similarly, other osteogenic stimuli such as mechanical stress, drugs, or cytokines exert their osteogenic effects through activation of p38 followed by an increase in Osx expression and function (17,(45)(46)(47). Our results provide a mechanism by which BMP-2-activated p38 could enhance transcriptional activity of Osx through direct phosphorylation on Ser-73 and Ser-77.…”
Section: Discussionmentioning
confidence: 99%
“…OPN reactivity in the cement line and surface of cementum and alveolar bone might be induced by osterix expression. Their strong localization in periodontal tissues when 100 g of heavy force was applied indicates that they might be molecules linking mechanostressing and osteogenic and odontogenic differentiation 20,23,24 and might be involved in bone, PDL, and cementum remodeling during orthodontic tooth movement. The precise relationship between OPN and osterix during periodontal tissue remodeling in response to heavy force could not be ascertained with the current methodology.…”
Section: Discussionmentioning
confidence: 99%